Implementation of Load Balancing Algorithms to Evaluate Performance Degradation Factors in Cloud Computing - Khalid, R. (Journal of Engineering and Technology (JET), 2016)
Cloud computing presents the idea of elastic and highly scalable networking resources provision as a service over the internet. It is an emerging internet-based computing where shared resources, data and information are provided on demand to the end users using computers and other devices. Cloud is a significant model to access the distributed computing resources. This research is based on evaluation of performance degradation factors in cloud computing. This research covers different strategies of performance evaluation in cloud computing. There are many factors that cover performance degradation in cloud networks and unlike traditional systems; it is difficult to reveal the degradation factors and their intensity. This research discovered different types of performance degradation factors and their magnitude in cloud computing. High performance is the essential key elements in cloud computing to make the cloud users happy. The objective of this study is to highlight the significance of parameters which can create the high performance of cloud computing. The aim of this study is to present progressive advancement in understanding the implications of cloud computing performance parameters. The approach of this study has been to undertake an evaluation of the technological factors affecting the cloud computing performance and to present idea to build highly scalable cloud environments. This research study has identified the metrics through which performance of the cloud network becomes unreliable and unsuitable. This research will be helpful for those who want to deploy new cloud infrastructure.